2015
DOI: 10.1007/s00436-015-4661-2
|View full text |Cite
|
Sign up to set email alerts
|

The field efficacy of Lepidium latifolium and Zataria multiflora methanolic extracts against Varroa destructor

Abstract: Varroa destructor is the most serious pest of honeybee (Apis mellifera), causing high economic losses in the beekeeping industry worldwide. The intensive utilization of many chemical substances against the mites resulted in resistance development. One of the applicable and alternative treatments being used for their control is plant-derived products (PDSS). The aim of this study was to evaluate the acaricidal activity of Lepidium latifolium and Zataria multiflora leaf extracts on V. destructor in field conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The use of natural products against varroosis is an eco-friendly approach to this severe problem. Field tests on the use of methanolic extracts of Lepidium latifolium and Zataria multiflora indicated that these preparations exhibited acaricidal activity against the mites [35]. However, there are no preceding data on the action of costic acid against varroa.…”
Section: Introductionmentioning
confidence: 99%
“…The use of natural products against varroosis is an eco-friendly approach to this severe problem. Field tests on the use of methanolic extracts of Lepidium latifolium and Zataria multiflora indicated that these preparations exhibited acaricidal activity against the mites [35]. However, there are no preceding data on the action of costic acid against varroa.…”
Section: Introductionmentioning
confidence: 99%
“…Plant-derived products, such as essential oils and methanolic extracts, are potential alternative agents to synthetic chemical products [28]. These substances are commonly used to maintain the social life of animals and to overcome issues of food safety and economics, because they are generally cost-effective and safe for both humans and animals [29]. Some efforts have been made to find more effective anti-hemosporidial compounds and some herbal products have been reported to be effective anti-malarial therapies [13].…”
Section: Discussionmentioning
confidence: 99%
“…Acaricide activity was determined to be the highest (100%) for L. latifolium extract at 500 ppm after 12 days and 86.26% for Z. multiflora. It has been reported that both extracts can be used for varroa on bees and that there are no acknowledged negative effects on honey bee colonies (Razavi, Asadpour, Jafari, & Malekpour, 2015). In another study performed in the same year, it was reported that 10 g of thyme added to bee cake had a mortality percentage of 92.85% in Varroa mite (Emsen & Dodoloğlu, 2015).…”
Section: Studies On Bee Health Of Medicinal Aromatic Plants and Oilsmentioning
confidence: 98%